Library, archival and information studies (LARIS) curricula as determinant of professional job performance in librarianship in Nigeria (2004)
A comparison of the performance of LARIS graduates with the departmental curricula was made with a view to identifying the strengths and weaknesses of LARIS graduâtes at their various places of work. The participants for the study consist of three hundred and ten (310) graduâtes of LARIS Department randomly selected. The four point Likert Scale fixed response questionnaire was used to obtain information on the perception of LARIS graduâtes on professional job performance. The t-test statistics was utilised to analyse the data collected for the study. The results indicated that significant relationship existed between the curricula and learning outcomes of LARIS graduâtes; the charactepstics of LARIS cirncula is not a determinant of professional job performance in the field of librarianship; and there is no noticeable professionalism in the field of librarianship in Nigeria at présent. The study then recommended improvement in the areas of teaching -learning activités; provision of library equipment and tools; and prompt appraisal of present LARIS curricula if the Department must meet its strategie rôles in elevating the standard of practicing librarians to a professional one in Nigeria.